RIFM fragrance ingredient safety assessment, 2(10)-pinen-3-ol, CAS Registry Number 5947-36-4. (December 2018) - Api, A.M.; Belsito, D.; Botelho, D.; Bruze, M.; Burton, G.A.; Buschmann, J.; Dagli, M.L.; Date, M.; Dekant, W.; Deodhar, C.; Francis, M.; Fryer, A.D.; et al.
Highlights: 2(10)-Pinen-3-ol, safety assessment based on RIFM's criteria. Safety assessment based on 7 human health endpoints plus environmental. All endpoints were cleared using target data, read-across, and/or TTC.